A Juridical Study Of Immaterial Compensation Lawsuit Decision 283/Pdt.G/2017/PN.JKT.PST - Dian Mayangsari, Arifiati; Najib Imanullah, Moch. (International Journal of Educational Research & Social Sciences, 2024)
This research aims to analyze Decision 283/Pdt.G/2017/PN.JKT.PST regarding the immaterial compensation lawsuit. The case's position was a patient named Siti Chomsatun, who sought treatment at Kramat 128 Hospital, Jakarta, where medical malpractice occurred, causing harm to the patient. Furthermore, the patient filed an immaterial compensation lawsuit against Kramat 128 Hospital Jakarta. This research was normative legal research with statutory, case, and conceptual approaches. The legal materials used consisted of primary and secondary legal materials. Primary legal materials were in the form of statutory regulations, and secondary legal materials were in the form of scientific works and documents. In the research results, Siti Chomsatun, as the plaintiff, filed a lawsuit for immaterial compensation against Kramat 128 Hospital Jakarta in Rp—300,000,000 due to physical suffering. The Court's decision on the plaintiff's lawsuit was not granted in full because the plaintiff could not prove the losses suffered. Meanwhile, no regulations strictly regulated the legal basis for immaterial losses.